Language policy in the Kazakh Soviet Socialist Republic in the years 1920–1940 - Zhumanova, A.Z. (Ye.A.Buketov Karaganda State University Publ., 2012)
The article is devoted to the topical issues of the language policy in the Kazakh Soviet Socialist Republic in 1920–1940. In the article we give consideration to one of the most favorable period of case history of national language system in Kazakhstan. We carry out a review of problematic situations occurred before the war time. Language situation and language development in the state are the most complicated and problematic issues of inter-ethnic relation regulation. To find reasonable ways to solve them means stability for society. To solve issues regarding state and legal regulation of language process is a quite difficult and ambiguous thing to do in the Constitution development both in the Former Kazakh SSR and in foreign countries. Everything depends on certain conditions and demands of society for use and development of a certain language, on combination of different languages.
1920–1940 жылдардағы Қазақ Кеңестік Социалистік Республикасындағы тіл саясаты
Языковая политика в Казахской Советской Социалистической Республике в 1920–1940 годы
Keywords: the USSR; the declaration; the Kazakh SSR; the session of the Supreme Council of the Kazakh Soviet Socialist Republic; the Council of People's Commissars